Application Electronic Procurement at the Bureau of Procurement of Goods/Services North Sumatra Province - Dedy Darmawan; Badaruddin Badaruddin; Humaizi Humaizi (Budapest International Research and Critics University, 2022)
This study aims to analyze the implementation of E-Procurement in the Bureau of Procurement of Goods and Services of North Sumatra Province, analyze the impacts experienced and the obstacles caused by the implementation of E-Procurement at the Bureau of Procurement of Goods and Services of North Sumatra Province, and analyze the role of E-Procurement in the Procurement Bureau. North Sumatra Province Goods and Services in minimizing fraud in the process of procurement of goods and services. This research is located at the Bureau of Procurement of Goods and Services, North Sumatra Province, namely the Goods and Services Procurement Unit and LPSE using descriptive qualitative research methods with in-depth interview techniques and observations with informants who are the E-Procurement implementation team and service providers who have received tenders and make observations, especially on the website and E-Catalogue. This research shows that the Bureau of Procurement of Goods and Services has implemented E-Procurement in accordance with the direction of the government, and the most perceived obstacle from this program is the knowledge of the implementers about the E-Procurement system and servers that are often down. The impact that is felt the most is the effectiveness of the process as well as the transparency and convenience that is felt by all parties.